2013
DOI: 10.1152/ajprenal.00644.2012
|View full text |Cite
|
Sign up to set email alerts
|

Human kidney-2 cells harbor functional dopamine D1 receptors that require Gfor Gq/11αsignaling

Abstract: A recent study demonstrated that the dopamine D1 receptor (D1R) is nonfunctional in human kidney cells, HK2 cells, in terms of their inability to couple to G s protein in response to the D1R agonist fenoldopam. Since D1R also couples to G q protein, we tested whether D1R is functional in HK2 cells in terms of their ability to couple to G q and produce downstream signaling. For comparison, we also studied another receptor, angiotensin II type 1 receptor (AT1R) known to couple to G q. Protein kinase C (PKC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Western immunoblotting in cytosolic and nuclear fractions and tissue homogenates were performed using standard methods as described previously [ 29 ]. Tissue homogenates were made in lysis buffer (mM: 20 Tris-HCl (pH 7.5), 150 NaCl, 1 Na 2 EDTA, 1 EGTA, 1% Triton, 2.5 sodium pyrophosphate, 1 beta-glycerophosphate, 1 Na 3 VO 4 , 1 μ g/mL leupeptin, and protease inhibitor cocktail) as described [ 29 ]. Protein concentrations in the cytosolic and nuclear fractions and in homogenates were determined by BCA protein assay kit (Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Western immunoblotting in cytosolic and nuclear fractions and tissue homogenates were performed using standard methods as described previously [ 29 ]. Tissue homogenates were made in lysis buffer (mM: 20 Tris-HCl (pH 7.5), 150 NaCl, 1 Na 2 EDTA, 1 EGTA, 1% Triton, 2.5 sodium pyrophosphate, 1 beta-glycerophosphate, 1 Na 3 VO 4 , 1 μ g/mL leupeptin, and protease inhibitor cocktail) as described [ 29 ]. Protein concentrations in the cytosolic and nuclear fractions and in homogenates were determined by BCA protein assay kit (Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Western immunoblotting on tissue homogenates and membranes was performed by standard methods as described previously (31). Briefly, tissue homogenates were made in lysis buffer (20mM Tris-HCl (pH 7.5),150mM NaCl, 1mM Na 2 EDTA, 1mM EGTA, 1% Triton, 2.5mM sodium pyrophosphate, 1mM beta-glycerophosphate, 1mM Na 3 VO 4 , 1 μg/ml leupeptin, protease inhibitor cocktail) as described.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, tissue homogenates were made in lysis buffer (20mM Tris-HCl (pH 7.5),150mM NaCl, 1mM Na 2 EDTA, 1mM EGTA, 1% Triton, 2.5mM sodium pyrophosphate, 1mM beta-glycerophosphate, 1mM Na 3 VO 4 , 1 μg/ml leupeptin, protease inhibitor cocktail) as described. Crude plasma membranes from tissues were also made in lysis buffer using our published method (31). Protein concentrations in the homogenate and membrane samples as well as in bladder urine were determined by the BCA protein assay kit (Pierce BCA Protein Assay Kit, Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, regulation of receptor function, including chemokine receptors, by concerted activity of G q and G i proteins has been described. Pokkunuri et al [50] reported a G q -mediated signaling of D1R and angiotensin receptor 1 in a G i -dependent manner in human kidney HK2 cells. They showed that signaling of the Ga q -coupled D1R receptor [51] was ablated in the presence of Ga q/11 small interfering RNA and by pretreatment with PTX.…”
Section: Discussionmentioning
confidence: 99%